A REVIEW ON GLOBAL TRENDS IN HEART FAILURE AND EVOLUTION OF ANGIOTENSIN–NEPRILYSIN INHIBITOR - UPPARA, VEERENDRA; KODIVANDLA, SAISEKHAR; ALI SHAIK, ASHIK (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Heart failure (HF) is a major global public health problem irrespective of its causes. It generates an enormous clinical, societal, and economic, health loss burden with an increase in its prevalence reaching an epidemic proportion. The morbidity and mortality associated with heart failure are increasing the health-related burdens worldwide, especially in low- and middle-income countries. This review highlights the trends in HF burden, the clinical spectrum of HF, and the importance of neurohormonal pathways and the evolution of angiotensin receptor neprilysin inhibition in HF with updated clinical practice guidelines.